Meanings of music in film from a cognitive perspective - Cieślak, Agnieszka (Interdisciplinary Studies in Musicology, 2019)
Cognitive psychology, with its focus on mind and its processes, is one of the approaches to study film music. Although music alone is said to be already meaningful, it gains and transfers specific meanings in the film context. This article aims to contribute to understanding of what film music means and how these meanings are processed in the cross-modal perception of a film. A review of the selected empirical research on film music with regard to meaning is followed by a short overview of the Annabel J. Cohen’s Congruence-Association Model (CAM) of media cognition. The model provides a framework for the experiments’ results and encourages future interdisciplinary studies in this area.